Contribution of Campus Theater on Multiple Intelegence Education - Musthofa Kamal (International Research-Based Education Journal, 2021)
Historically, theater is one of the oldest known activities. When a community will gather for a ceremonial purpose: hoping for a good game, asking for rain, or praying a long life for the new leader. Theatrical elements present in these ceremonial activities, for example, appear in singing, dancing, storytelling, and dressing up in costumes and masks of gods and animals. The actors play roles according to their respective capacities in the ceremonial activity of the ritual.